Pengembangan Strategi Digital Marketing untuk Meningkatkan Penjualan dan Persebaran Tenun Leny Bumpak - Agustina, Cica; Aszahrah, Radiah; Syabirin, Noval; Zaki, Khozin; Indra, Yetti Afrida (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Leny Bumpak Weaving Craft is a local cultural heritage from Seluma Regency, Bengkulu, which has high historical and aesthetic value. However, limitations in digital promotion and marketing strategies have caused this woven product to be less widely known, especially in today's digital era. This activity aims to increase sales and distribution of Leny Bumpak weaving through Digital Marketing based on the strategies carried out. The approach taken is educational and participatory which actively involves participants in the process of activities starting from identifying problems to implementing predetermined programs. The results of the study showed that the digital marketing strategy carried out had a very positive effect on sales and distribution of Leny Bumpak weaving.